TRANSLANGUAGING IN INDONESIAN UNIVERSITY CLASSROOM CONTEXT: A DISCOURSE ANALYSIS AT MUHAMMADIYAH UNIVERSITY IN SOUTH SULAWESI - Wongso Adi Saputra; Haryanto Atmowardoyo (ELT Worldwide: Journal of English Language Teaching, 2015)
In teaching and learning process of the L2, the use of L1 in mediating the learning is needed to be considered. Therefore, this article aimed at finding out the support of the translanguaging on TEFL since translanguaging is the way of functioning L1 in teaching L2. The qualitative method was done in this research. The subjects were two English lecturers of Muhammadiyah University of Makassar in English Teaching and Training Department. The data were collected through interviewing and observing those two lecturers in the classroom teaching and learning process. Then, in addition to the data, those lecturers’ students were interviewed in order to dig their perception of the used of translanguaging in the L2 acquiring process. Furthermore, the data were analyzed using descriptive qualitative analysis. In the research findings there were five types of translanguaging as the way of the L1 and the L2 interacted each other in the classroom that used by the lecturers in teaching and learning process. Besides, there were ten functions of translanguaging as the action toward the L1 and the L2 in the classroom. Furthermore, translanguaging gives the support on TEFL in the classroom context. Key words: Translanguaging, First Language (L1), Second Language (L2).